Factors that influence the implementation time of bridge projects - Sholihin, Rohmat Agus; Suroso, Agus; Amin, Mawardi (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
Delays are common in project implementation, even in bridge construction projects. It is important to analyze the causes of these delays so that service providers and construction parties can take appropriate measures to overcome the problem. These measures can help reduce the costs associated with delays. The research aims factors that influence the performance of bridge project implementation times, and to find alternative solutions to resolve these factors. The research uses a quantitative method. Primary data is obtained through questionnaires distributed to respondents among bridge construction practitioners on three predetermined research objects: Desari, Cisumdawu, and Cijago toll road projects sections 2-3. The research data is processed using JASP software. After analyzing the implementation methods, budget availability, and engineering risk variables, it is found that engineering risk is the most dominant factor affecting the performance of bridge project implementation time, with a percentage of 61.68%.